Preparation method of gradient core-shell structure steel slag-based expansive aggregate and concrete material thereof
Patent Information
- Application Number
- CN202611047025.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-15
AI Technical Summary
[0005]针对上述的问题,本发明提供一种梯度核壳结构钢渣基膨胀骨料的制备方法及其混凝土材料,该钢渣骨料可在24~72小时窗口内集中水化释放膨胀效应,从而补偿UHPC的自收缩,有效缓解了UHPC由于自收缩引发的微裂纹造成的力学性能下降的问题
针对钢渣的水化诱导期长,活性释放时间分散、速率不稳定,难以在特定时间窗口内集中激发形成膨胀性产物补偿UHPC的早期自收缩的问题,本发明在钢渣骨料表面构建从内向外分布的致密化学键合层、功能阻隔层、敏感响应层梯度结构,从而使钢渣骨料可在24~72小时窗口内集中水化释放膨胀效应补偿UHPC的早期自收缩,有效缓解了UHPC由于自收缩造成的力学性能下降的问题。首先,所述敏感响应层中的VAE共聚物基体由于含有醋酸酯基团,其在UHPC提供的高碱性环境下发生水解后的水解产物与混凝土中的钙离子进一步反应形成乙酸钙([-CH2-CH(OCOCH3)-]n+OH-+Ca2+→[-CH2-CH(OH)-]n+Ca(CH3COO)2)。而所述乙酸钙会溶出至UHPC基体中,再加上这一反应在UHPC提供的水化热作用下加速进行,从而在所述敏感响应层中形成微孔隙。UHPC基体中的水分通过所述微孔隙逐渐向内部进行有限的渗透,此时所述功能阻隔层保持完整,且其中均匀分布的所述ExLDH构建的“迷宫效应”可有效延长水分子和离子的扩散路径,使本发明的钢渣基膨胀骨料在水化初期(0~24小时左右)能够精确控制水分渗透速率,确保骨料中的钢渣在这一时期保持稳定,因为此阶段UHPC的自收缩不明显,如果钢渣提前发挥效果,容易造成后期的自收缩无法得到有效补偿。随着所述UHPC中水化反应的不断进行(24~48小时左右),所述敏感响应层中逐渐形成裂纹,但在所述PLDH的作用下阻止裂纹连接形成通道,从而仍然保持一定的阻水功能。此时,与所述功能阻隔层接触的水分渗透速率有所提升,但仍然保持良好的“迷宫效应”,进入到所述钢渣基膨胀骨料内核中的少量水分使钙基激发剂溶解后对钢渣进行预激活。随着水化反应的进一步进行(48~72小时左右),所述敏感响应层基本崩解,功能阻隔层也逐渐在碱性环境下崩解后失去延长水分子和离子的扩散路径的“迷宫效应”,所述PLDH、ExLDH层间作为电荷平衡的碳酸根离子逐渐被混凝土中的氢氧根离子部分置换后导致层间距增大,进而造成包覆层结构剥落,所述致密化学键合层也同步水解失效,水分子大量进入到经过预激活的所述内核中触发膨胀集中释放:其中的硫酸盐溶解释放硫酸根离子进入到混凝土基体中,并与水泥组分中的铝酸三钙及钢渣溶出的活性铝酸根反应生成膨胀性产物钙矾石,与UHPC自收缩最剧烈的时段相匹配,实现对收缩的同步补偿。同时,所述钢渣在钙基激发剂的作用下进行水化反应形成无定形C-S-H凝胶,进一步提升UHPC的力学性能。本发明通过在梯度结构构建特殊的梯度结构,并且对功能阻隔层和敏感响应层中的镁铝水滑石进行差异化功能改性,形成多机制时序控释,实现了钢渣释放的膨胀与UHPC自收缩峰值时段相匹配,克服了UHPC由于自收缩造成的力学性能下降的问题。
Smart Images

Figure CN122541120B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a method for preparing a gradient core-shell structure steel slag-based expansive aggregate and its concrete material. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Steel slag is a large-scale industrial solid waste generated during steelmaking. It contains active mineral components such as free calcium oxide, dicalcium silicate, and tricalcium silicate, exhibiting potential hydration activity. However, steel slag has low early hydration activity, and the hydration induction period of free calcium oxide is long, typically only beginning to show significant hydration after seven days. Furthermore, the release of activity is dispersed and the rate is unstable, making it difficult to concentrate and activate within a specific time window. Ultra-high performance concrete (UHPC) suffers from significant early autogenous shrinkage due to its large amount of cementitious materials and extremely low water-cement ratio. Studies have shown that early shrinkage (≤7 days) accounts for 61.3%–86.5% of the total shrinkage in UHPC, with autogenous shrinkage accounting for approximately 78.6%–90% of this, which is the main cause of early cracking in UHPC. If steel slag is directly added to UHPC, the hydration reaction of the free calcium oxide and free magnesium oxide in the dense matrix of UHPC is extremely slow. It often does not begin to occur significantly until weeks or even months after the concrete has set and hardened. The resulting delayed expansion phenomenon lacks sufficient buffer space due to the extremely low water-cement ratio and extremely low permeability of UHPC. It is very easy to accumulate huge expansion stress locally and induce microcracks or even macro-cracks.
[0004] Furthermore, the low hydration activity of steel slag can delay the early hydration process of UHPC and disrupt the synergistic effect between cementitious components, resulting in a significant decrease in early compressive strength. The effect of steel slag on the shrinkage behavior of UHPC is not a simple monotonic compensation; the resulting volume effect is the result of the coupling of multiple contradictory mechanisms, making it difficult to achieve reliable shrinkage control through simple dosage adjustments. Therefore, simply adding steel slag to UHPC not only fails to effectively solve the cracking problem caused by early autogenous shrinkage but also introduces multiple potential cracking factors and durability risks, making it difficult to meet the core requirements of UHPC for reliability and long-term stability. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a method for preparing a gradient core-shell structure steel slag-based expansive aggregate and its concrete material. This steel slag aggregate can concentrate on hydration and release its expansion effect within a 24-72 hour window, thereby compensating for the autogenous shrinkage of UHPC and effectively alleviating the problem of decreased mechanical properties caused by microcracks in UHPC due to autogenous shrinkage. Specifically, the technical solution of this invention is as follows.
[0006] In a first aspect of the present invention, a method for preparing a gradient core-shell structured steel slag-based expansive aggregate is provided, comprising the following steps: (1) Provide core particles composed of steel slag powder, calcium-based activator and sulfate for later use.
[0007] (2) Apply a coupling agent dilution to the surface of the core particles and heat it. After completion, apply a composite liquid formed by ethylene-vinyl acetate copolymer (VAE) emulsion and coupling agent to the surface of the pretreated particles. After drying and curing, obtain Grade I core-shell particles for later use.
[0008] (3) Methyl methacrylate (MMA) was added to the magnesium aluminum hydrotalcite powder dispersion a, and then an initiator was added under a protective atmosphere before heating and stirring to react. After completion, the solid product was separated, washed, dried, and ground to obtain PMMA hybrid exfoliated LDH (ExLDH). Then, the exfoliated LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid a, which was then applied to the surface of the first-level core-shell particles. After drying and curing, the second-level core-shell particles were obtained.
[0009] (4) Methyl methacrylate (MMA) and / or hydroxyethyl acrylate (HEA) and a crosslinking agent are added to the magnesium aluminum hydrotalcite powder dispersion b and mixed well. Then, an initiator is added under a protective atmosphere and the mixture is heated and stirred to react. After completion, the solid product is separated, washed, dried, and ground to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water are mixed to form a coating liquid b. The coating liquid b is then applied to the surface of the Class II core-shell particles, dried, and cured to obtain the steel slag-based expanded aggregate.
[0010] Further, in step (1), the ratio of steel slag powder, calcium-based activator, and sulfate is 70-80 parts by weight: 5-10 parts by weight: 2-4 parts by weight. Optionally, in step (1), the specific surface area of the steel slag powder is 400-500 m². 2 / kg.
[0011] Further, in step (1), the calcium-based activator is an active powder obtained by calcining limestone at 1200-1400℃ for 5-15 minutes. Optionally, the specific surface area of the calcium-based activator is 450-550 m². 2 / kg.
[0012] Furthermore, in step (1), the particle size of the core particles is 0.45~2mm.
[0013] Further, in step (2), the coupling agent diluent is 0.2-0.5% of the mass of the core particles.
[0014] Further, in step (2), the coupling agent dilution solution is prepared by mixing the coupling agent, anhydrous ethanol, and water in a volume ratio of 1:1:7~8.5. Optionally, the coupling agent includes at least one of KH-550, KH-560, KH-570, KH-792, KH-171, A-151, etc.
[0015] Further, in step (2), the heating and heat preservation temperature is 45~55℃, and the time is 5~10min. During this process, the coupling agent hydrolyzes and reacts with the silanol groups on the surface of the core particles to form -Si-O-Si- chemical bonds, thereby forming a base layer on the surface of the core particles, which facilitates the coating of the composite liquid into a film.
[0016] Further, in step (2), the mass fraction of the coupling agent in the composite liquid is 0.5~1%. Optionally, the coupling agent includes at least one of KH-550, KH-560, KH-570, KH-792, KH-171, A-151, etc.
[0017] Further, in step (2), the composite liquid is 5-8% of the mass of the pretreated particles. Optionally, the solid content of the ethylene-vinyl acetate copolymer (VAE) emulsion in the composite liquid is 35-42 wt.%.
[0018] Further, in step (2), the drying and curing temperature is 45~55℃, and the time is 5~10min. During this process, after the VAE in the composite liquid is cured, a dense chemically bonded layer is constructed on the substrate layer on the surface of the pretreated particles, thereby transforming the core particles into Class I core-shell particles.
[0019] Further, in step (3), the mass ratio of methyl methacrylate (MMA) to magnesium aluminum hydrotalcite powder in dispersion a is 0.5~1.5:1. Optionally, the solid content of the magnesium aluminum hydrotalcite powder dispersion a is 20~30 wt.%.
[0020] Further, in step (3), the initiator is 0.5-1.5% of the mass of methyl methacrylate (MMA). Optionally, the initiator includes at least one of ammonium persulfate (APS), azobisisobutyronitrile (AIBN), etc.
[0021] Further, in step (3), the heating and stirring reaction is carried out at a temperature of 60-80°C for 4-8 hours. During this process, the MMA is polymerized in situ between the layers of magnesium aluminum hydrotalcite (LDH) to form PMMA, thereby exfoliating the magnesium aluminum hydrotalcite into single-layer or oligolayer nanosheets.
[0022] Further, in step (3), the mass ratio of VAE dry matter in the stripped LDH to ethylene-vinyl acetate copolymer (VAE) emulsion is 1:4~6. Optionally, the water content of the coating solution a is 40~60 wt.%.
[0023] Furthermore, in step (3), the coating liquid a is 6-10% of the mass of the Class I core-shell particles.
[0024] Further, in step (3), the drying and curing temperature is 50~60℃ and the time is 10~15min. During this process, after the dispersion is cured, a functional barrier layer is constructed on the surface of the first-level core-shell particles, thereby forming second-level core-shell particles. The ExLDH forms a highly oriented and uniformly dispersed layer in the functional barrier layer, creating a "maze effect" to prolong the diffusion path of water molecules and ions, thereby precisely controlling the water penetration rate.
[0025] Further, in step (4), the mass ratio of methyl methacrylate (MMA) and / or hydroxyethyl acrylate (HEA) to the magnesium aluminum hydrotalcite powder in dispersion b is 0.5~1.5:1. Optionally, the solid content of the magnesium aluminum hydrotalcite powder dispersion b is 20~30 wt.%.
[0026] Further, in step (4), the crosslinking agent is 2-8% by mass of methyl methacrylate (MMA) and / or hydroxyethyl acrylate (HEA). Optionally, the crosslinking agent includes at least one of ethylene glycol dimethacrylate (EGDMA), N,N'-methylenebisacrylamide (MBA), triethylene glycol diacrylate (TEGDA), and 1,6-hexanediol diacrylate (HDODA).
[0027] Further, in step (4), the initiator is 0.5-1.5% by mass of methyl methacrylate (MMA) and / or hydroxyethyl acrylate (HEA). Optionally, the initiator includes at least one of ammonium persulfate (APS), azobisisobutyronitrile (AIBN), etc.
[0028] Further, in step (4), the heating and stirring reaction is carried out at a temperature of 60-80°C for 4-8 hours. The methyl methacrylate (MMA) and / or hydroxyethyl acrylate (HEA) are polymerized in situ in the interlayer of magnesium aluminum hydrotalcite (LDH) to form a cross-linked polymer network, thereby obtaining the cross-linked polymer intercalation modified LDH (PLDH).
[0029] Further, in step (4), the mass ratio of the dry matter of the VAE in the crosslinked polymer intercalated modified LDH to the ethylene-vinyl acetate copolymer (VAE) emulsion is 1:2~3. Optionally, the water content of the coating solution b is 40~60 wt.%.
[0030] Furthermore, in step (4), the coating liquid b is 4-7% of the mass of the Class II core-shell particles.
[0031] Furthermore, in step (4), the drying and curing temperature is 60~70℃ and the time is 2~3 hours.
[0032] In a second aspect of the present invention, an ultra-high performance concrete material is provided, comprising the following components in the following proportions: 90-110 parts by weight of cement, 20-30 parts by weight of silica fume, 50-90 parts by weight of fine aggregate, 15-50 parts by weight of the steel slag-based expansive aggregate of the present invention, 1.5-4 parts by weight of water-reducing agent, and 10-30 parts by weight of steel fiber.
[0033] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: To address the issues of long hydration induction period, dispersed and unstable activity release time and rate in steel slag, making it difficult to concentrate the formation of expansive products to compensate for the early self-shrinkage of UHPC within a specific time window, this invention constructs a gradient structure on the surface of steel slag aggregate, consisting of a dense chemically bonded layer, a functional barrier layer, and a sensitive response layer distributed from the inside out. This allows the steel slag aggregate to concentrate on hydration and release the expansion effect within a 24-72 hour window to compensate for the early self-shrinkage of UHPC, effectively alleviating the problem of decreased mechanical properties of UHPC due to self-shrinkage. Firstly, the VAE copolymer matrix in the sensitive response layer contains acetate groups. Its hydrolysis products, after hydrolysis in the highly alkaline environment provided by UHPC, further react with calcium ions in the concrete to form calcium acetate ([-CH2-CH(OCOCH3)-). n +OH - +Ca 2+ →[-CH2-CH(OH)-] n+Ca(CH3COO)2). The calcium acetate dissolves into the UHPC matrix, and this reaction is accelerated by the hydration heat provided by the UHPC, thus forming micropores in the sensitive response layer. Water in the UHPC matrix gradually permeates into the interior through these micropores in a limited manner. At this time, the functional barrier layer remains intact, and the "maze effect" constructed by the uniformly distributed ExLDH effectively prolongs the diffusion path of water molecules and ions. This allows for precise control of the water permeation rate in the initial stage of hydration (approximately 0-24 hours) of the steel slag-based expanded aggregate of the present invention, ensuring that the steel slag in the aggregate remains stable during this period. This is because the autogenous shrinkage of UHPC is not significant at this stage. If the steel slag takes effect prematurely, it may cause the autogenous shrinkage in the later stage to be unable to be effectively compensated. As the hydration reaction in the UHPC continues (approximately 24-48 hours), cracks gradually form in the sensitive response layer, but the PLDH prevents the cracks from connecting and forming channels, thus maintaining a certain water-blocking function. At this point, the water penetration rate in contact with the functional barrier layer increases, but the "maze effect" is still maintained. A small amount of water entering the core of the steel slag-based expansive aggregate dissolves the calcium-based activator and pre-activates the steel slag. As the hydration reaction progresses further (around 48-72 hours), the sensitive response layer basically disintegrates, and the functional barrier layer also gradually disintegrates in the alkaline environment, losing the "maze effect" of extending the diffusion path of water molecules and ions. The carbonate ions that serve as charge balance between the PLDH and ExLDH layers are gradually partially replaced by hydroxide ions in the concrete, leading to an increase in interlayer spacing, which in turn causes the coating structure to peel off. The dense chemical bonded layer also hydrolyzes and fails simultaneously. A large number of water molecules enter the pre-activated core, triggering a concentrated release of expansion: the sulfate dissolves and releases sulfate ions into the concrete matrix, which react with tricalcium aluminate in the cement components and active aluminate dissolved from the steel slag to generate the expansive product ettringite, matching the period of most intense self-shrinkage of UHPC, thus achieving synchronous compensation for shrinkage. Simultaneously, the steel slag undergoes a hydration reaction under the action of a calcium-based activator to form an amorphous CSH gel, further enhancing the mechanical properties of UHPC. This invention, by constructing a special gradient structure and differentially modifying the magnesium aluminum hydrotalcite in the functional barrier layer and sensitive response layer, forms a multi-mechanism time-sequential controlled release, achieving a match between the expansion released by the steel slag and the peak period of UHPC self-shrinkage, overcoming the problem of decreased mechanical properties of UHPC due to self-shrinkage. Attached Figure Description
[0034] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention and do not constitute an undue limitation of the invention.
[0035] Figure 1The image shows a sample of steel slag-based expanded aggregate prepared in Example 1 below.
[0036] Figure 2 The image shows a sample of steel slag-based expanded aggregate prepared in Example 2 below.
[0037] Figure 3 The image shows a sample of steel slag-based expanded aggregate prepared in Example 3 below.
[0038] Figure 4 The image shows a sample of steel slag-based expanded aggregate prepared in Example 4 below.
[0039] Figure 5 The image shows a sample of steel slag-based expanded aggregate prepared in Example 5 below.
[0040] Figure 6 The image shows a sample of steel slag-based expanded aggregate prepared in Example 6 below.
[0041] Figure 7 The image shows a sample of steel slag-based expanded aggregate prepared in Example 7 below. Detailed Implementation
[0042] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as those skilled in the art. The preferred embodiments and materials described in this invention are for illustrative purposes only. The technical solutions of the present invention will now be further described with reference to specific embodiments.
[0043] Example 1 1. A method for preparing a gradient core-shell structured steel slag-based expansive aggregate, comprising the following steps: (1) The following components are used: 75 parts by weight of converter steel slag powder, 8 parts by weight of calcium-based activator, and 2.5 parts by weight of sodium sulfate, wherein the specific surface area of the steel slag powder is 463.9 m². 2 / kg, the calcium-based activator is obtained by grinding limestone after calcination at 1350℃ for 10 min, resulting in a specific surface area of 517.4 m². 2 / kg of active powder. The mixed powder obtained by uniformly mixing the above components is added to a disc granulator, and a composite binder solution of 10% by mass of the mixed powder is sprayed into it for granulation. After completion, it is dried at 60℃ for 20 minutes. The resulting particles are sieved, and particles with a particle size distribution between 0.45 and 2 mm are used as core particles for later use. The composite binder solution is prepared by mixing 1% by mass of hydroxypropyl methylcellulose aqueous solution and 15% by mass of water glass (modulus 2.4) at a volume ratio of 9:1.
[0044] (2) A silane coupling agent (KH550), anhydrous ethanol, and water were mixed evenly at a volume ratio of 1:1:8 to obtain a diluted coupling agent solution. Then, 0.3% of the diluted coupling agent solution by mass was sprayed onto the core particles under stirring, and then heated to 45°C and kept at that temperature for 10 minutes. After completion, pretreated particles were obtained.
[0045] (3) Add silane coupling agent (KH550) to an ethylene-vinyl acetate copolymer (VAE) emulsion with a solid content of 40 wt.% and stir until homogeneous to obtain a composite liquid with a coupling agent mass fraction of 0.65%. Then, spray 7% of the composite liquid onto the surface of the pretreated particles while stirring. After completion, heat to 45°C and keep at that temperature for 10 min for drying and curing to obtain Grade I core-shell particles for later use.
[0046] (4) Methyl methacrylate (MMA) was added to a magnesium aluminum hydrotalcite powder dispersion a with a solid content of 25 wt.%, and the mass ratio of MMA to magnesium aluminum hydrotalcite powder was 1:1. Then, under a nitrogen protective atmosphere, 1.5% by mass of the initiator (ammonium persulfate) of the MMA was added, and the mixture was heated to 70°C and stirred for 6 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain PMMA hybrid exfoliated LDH (ExLDH). Then, the exfoliated LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid a with a water content of 45 wt.%, wherein the mass ratio of the exfoliated LDH to the dry matter of VAE in the emulsion was 1:5. Then, 10% by mass of the coating liquid a was sprayed onto the surface of the Class I core-shell particles under stirring. After completion, the mixture was heated to 55°C and kept at that temperature for 12 minutes for drying and curing to obtain Class II core-shell particles.
[0047] (5) Methyl methacrylate (MMA) and a crosslinking agent (ethylene glycol dimethacrylate) were added to a magnesium aluminum hydrotalcite powder dispersion b with a solid content of 25 wt.% and stirred until homogeneous. The mass ratio of MMA to magnesium aluminum hydrotalcite powder was 1:1, and the crosslinking agent was 4.5% of the mass of MMA. Then, under a nitrogen protective atmosphere, 1.5% of the mass of MMA initiator (ammonium persulfate) was added and the mixture was heated to 70°C and stirred for 6 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid b with a water content of 45 wt.%, wherein the mass ratio of the intercalated modified LDH to the dry matter of VAE in the emulsion was 1:3. Then, while stirring, 5% by mass of the coating liquid b is sprayed onto the surface of the Class II core-shell particles. After completion, the mixture is heated to 65°C and held at that temperature for 2.5 hours for drying and curing to obtain the steel slag-based expanded aggregate (e.g. Figure 1 (As shown).
[0048] 2. A method for preparing ultra-high performance concrete material, comprising the following steps: The following components are selected: 100 parts by weight of 42.5 ordinary Portland cement, 25 parts by weight of silica fume, 70 parts by weight of quartz sand (particle size distribution between 0.45 and 2 mm), 30 parts by weight of the steel slag-based expansive aggregate described in this embodiment, 3 parts by weight of polycarboxylate superplasticizer, and 20 parts by weight of steel fiber. The above components are mixed with 22.5 parts by weight of water and stirred until homogeneous to obtain the ultra-high performance concrete material.
[0049] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GB / T 17671-2021) and ASTM C1698-2009, respectively. The results were: 28-day compressive strength = 167.4 MPa, 72-hour autogenous shrinkage = 407.5 μm / m.
[0050] Example 2 1. A method for preparing a gradient core-shell structured steel slag-based expansive aggregate, comprising the following steps: (1) The following components are taken in proportion: 70 parts by weight of converter steel slag powder, 5 parts by weight of calcium-based activator, and 2 parts by weight of sodium sulfate, wherein the specific surface area of the steel slag powder is 499.8 m². 2 / kg, the calcium-based activator is obtained by grinding limestone after calcination at 1400℃ for 5 minutes, resulting in a specific surface area of 550.1 m². 2 / kg of active powder. The mixed powder obtained by uniformly mixing the above components is added to a disc granulator, and a composite binder solution of 8% by mass of the mixed powder is sprayed into it for granulation. After completion, it is dried at 60℃ for 20 minutes. The resulting particles are sieved, and particles with a particle size distribution between 0.45 and 2 mm are used as core particles for later use. The composite binder solution is prepared by mixing 1% by mass of hydroxypropyl methylcellulose aqueous solution and 15% by mass of water glass (modulus 2.4) at a volume ratio of 9.5:0.5.
[0051] (2) A silane coupling agent (KH560), anhydrous ethanol, and water were mixed evenly at a volume ratio of 1:1:7 to obtain a diluted coupling agent solution. Then, 0.2% of the diluted coupling agent solution by mass was sprayed onto the core particles under stirring, and then heated to 50°C and kept at that temperature for 8 minutes. After completion, pretreated particles were obtained.
[0052] (3) Add silane coupling agent (KH560) to an ethylene-vinyl acetate copolymer (VAE) emulsion with a solid content of 35 wt.% and stir until homogeneous to obtain a composite liquid with a coupling agent mass fraction of 0.5%. Then, spray 8% of the composite liquid onto the surface of the pretreated particles while stirring. After completion, heat to 50°C and keep at that temperature for 8 min for drying and curing to obtain Grade I core-shell particles for later use.
[0053] (4) Methyl methacrylate (MMA) was added to a magnesium aluminum hydrotalcite powder dispersion a with a solid content of 20 wt.%, and the mass ratio of MMA to magnesium aluminum hydrotalcite powder was 0.5:1. Then, under a nitrogen protective atmosphere, 0.5% of the mass of the MMA initiator (ammonium persulfate) was added, and the mixture was heated to 80°C and stirred for 4 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain PMMA hybrid exfoliated LDH (ExLDH). Then, the exfoliated LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid a with a water content of 40 wt.%, wherein the mass ratio of the exfoliated LDH to the dry matter of VAE in the emulsion was 1:4. Then, 6% of the mass of the coating liquid a was sprayed onto the surface of the Class I core-shell particles under stirring. After completion, the mixture was heated to 50°C and kept at that temperature for 15 min for drying and curing to obtain Class II core-shell particles.
[0054] (5) Methyl methacrylate (MMA) and a crosslinking agent (N,N'-methylenebisacrylamide) were added to a magnesium aluminum hydrotalcite powder dispersion b with a solid content of 20 wt.% and stirred until homogeneous. The mass ratio of MMA to magnesium aluminum hydrotalcite powder was 0.5:1, and the crosslinking agent was 2% of the mass of MMA. Then, under a nitrogen protective atmosphere, 0.5% of the mass of MMA initiator (ammonium persulfate) was added and the mixture was heated to 80°C and stirred for 4 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid b with a water content of 40 wt.%, wherein the mass ratio of the intercalated modified LDH to the dry matter of VAE in the emulsion was 1:2.5. Then, under stirring, 4% by mass of the coating liquid b is sprayed onto the surface of the Class II core-shell particles. After completion, the mixture is heated to 60°C and held for 3 hours for drying and curing to obtain the steel slag-based expanded aggregate (e.g. Figure 2 (As shown).
[0055] 2. A method for preparing ultra-high performance concrete material, comprising the following steps: The following components are selected: 90 parts by weight of 42.5 ordinary Portland cement, 20 parts by weight of silica fume, 50 parts by weight of quartz sand (particle size distribution between 0.45 and 2 mm), 15 parts by weight of the steel slag-based expansive aggregate described in this embodiment, 1.5 parts by weight of polycarboxylate superplasticizer, and 10 parts by weight of steel fiber. The above components are mixed with 16.5 parts by weight of water and stirred until homogeneous to obtain the ultra-high performance concrete material.
[0056] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 165.1 MPa, 72-hour autogenous shrinkage = 432.9 μm / m.
[0057] Example 3 1. A method for preparing a gradient core-shell structured steel slag-based expansive aggregate, comprising the following steps: (1) The following components are taken in proportion: 80 parts by weight of converter steel slag powder, 10 parts by weight of calcium-based activator, and 4 parts by weight of sodium sulfate, wherein the specific surface area of the steel slag powder is 400.2 m². 2 / kg, the calcium-based activator is obtained by grinding limestone after calcination at 1200℃ for 15 min, resulting in a specific surface area of 449.7 m². 2 / kg of active powder. The mixed powder obtained by uniformly mixing the above components is added to a disc granulator, and a composite binder solution of 10% by mass of the mixed powder is sprayed into it for granulation. After completion, it is dried at 60℃ for 20 minutes. The resulting particles are sieved, and particles with a particle size distribution between 0.45 and 2 mm are used as core particles for later use. The composite binder solution is prepared by mixing 1% by mass of hydroxypropyl methylcellulose aqueous solution and 10% by mass of water glass (modulus 2.4) at a volume ratio of 9.5:0.5.
[0058] (2) A silane coupling agent (KH792), anhydrous ethanol, and water were mixed evenly at a volume ratio of 1:1:8.5 to obtain a diluted coupling agent solution. Then, 0.5% of the diluted coupling agent solution by mass was sprayed onto the core particles under stirring, and then heated to 55°C and kept at that temperature for 5 minutes. After completion, pretreated particles were obtained.
[0059] (3) Add silane coupling agent (KH792) to an ethylene-vinyl acetate copolymer (VAE) emulsion with a solid content of 42 wt.% and stir until homogeneous to obtain a composite liquid with a coupling agent mass fraction of 1%. Then, spray 5% of the composite liquid onto the surface of the pretreated particles while stirring. After completion, heat to 55°C and keep at that temperature for 5 min for drying and curing to obtain Grade I core-shell particles for later use.
[0060] (4) Methyl methacrylate (MMA) was added to a magnesium aluminum hydrotalcite powder dispersion a with a solid content of 30 wt.%, and the mass ratio of MMA to magnesium aluminum hydrotalcite powder was 1.5:1. Then, under a nitrogen protective atmosphere, 1.0% of the mass of the MMA initiator (azobisisobutyronitrile) was added, and the mixture was heated to 60°C and stirred for 8 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain PMMA hybrid exfoliated LDH (ExLDH). Then, the exfoliated LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid a with a water content of 60 wt.%, wherein the mass ratio of the exfoliated LDH to the dry matter of VAE in the emulsion was 1:6. Then, 7.5% of the mass of the coating liquid a was sprayed onto the surface of the Class I core-shell particles under stirring. After completion, the mixture was heated to 60°C and kept at that temperature for 10 minutes for drying and curing to obtain Class II core-shell particles.
[0061] (5) Hydroxyethyl acrylate (HEA) and a crosslinking agent (triethylene glycol diacrylate) were added to a magnesium aluminum hydrotalcite powder dispersion b with a solid content of 20 wt.% and stirred until homogeneous. The mass ratio of HEA to magnesium aluminum hydrotalcite powder was 1.5:1, and the crosslinking agent was 8% of the mass of HEA. Then, under a nitrogen protective atmosphere, 1.0% of the mass of HEA initiator (azobisisobutyronitrile) was added and the mixture was heated to 60°C and stirred for 8 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 300-mesh sieve to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid b with a water content of 60 wt.%, wherein the mass ratio of the intercalated modified LDH to the dry matter of VAE in the emulsion was 1:2. Then, under stirring, 7% by mass of the coating liquid b is sprayed onto the surface of the Class II core-shell particles. After completion, the mixture is heated to 70°C and held for 2 hours for drying and curing to obtain the steel slag-based expanded aggregate (e.g. Figure 3 (As shown).
[0062] 2. A method for preparing ultra-high performance concrete material, comprising the following steps: The following components are selected: 110 parts by weight of 42.5 ordinary Portland cement, 30 parts by weight of silica fume, 90 parts by weight of quartz sand (particle size distribution between 0.45 and 2 mm), 50 parts by weight of the steel slag-based expansive aggregate described in this embodiment, 4 parts by weight of polycarboxylate superplasticizer, and 30 parts by weight of steel fiber. The above components are mixed with 28 parts by weight of water and stirred until homogeneous to obtain the ultra-high performance concrete material.
[0063] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 170.4 MPa, 72-hour autogenous shrinkage = 347.3 μm / m.
[0064] Example 4 A method for preparing ultra-high performance concrete material includes the following steps: The following components are selected: 100 parts by weight of 42.5 ordinary Portland cement, 25 parts by weight of silica fume, 70 parts by weight of quartz sand (particle size distribution between 0.45 and 2 mm), 30 parts by weight of steel slag-based expansive aggregate, 3 parts by weight of polycarboxylate superplasticizer, and 20 parts by weight of steel fiber, wherein: the steel slag-based expansive aggregate is the Class II core-shell particles of Example 1 above (such as...). Figure 4 (As shown). The above components are mixed with 22.5 parts by weight of water and stirred evenly to obtain the ultra-high performance concrete material.
[0065] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 158.2 MPa, 72-hour autogenous shrinkage = 560.6 μm / m.
[0066] Example 5 A method for preparing ultra-high performance concrete material is the same as in Example 1 above, except that the steel slag-based expansive aggregate in this example is prepared using the following method: (1) The following components are used: 75 parts by weight of converter steel slag powder, 8 parts by weight of calcium-based activator, and 2.5 parts by weight of sodium sulfate, wherein the specific surface area of the steel slag powder is 463.9 m². 2 / kg, the calcium-based activator is obtained by grinding limestone after calcination at 1350℃ for 10 min, resulting in a specific surface area of 517.4 m². 2 / kg of active powder. The mixed powder obtained by uniformly mixing the above components is added to a disc granulator, and a composite binder solution of 10% by mass of the mixed powder is sprayed into it for granulation. After completion, it is dried at 60℃ for 20 minutes. The resulting particles are sieved, and particles with a particle size distribution between 0.45 and 2 mm are used as core particles for later use. The composite binder solution is prepared by mixing 1% by mass of hydroxypropyl methylcellulose aqueous solution and 15% by mass of water glass (modulus 2.4) at a volume ratio of 9:1.
[0067] (2) A silane coupling agent (KH550), anhydrous ethanol, and water were mixed evenly at a volume ratio of 1:1:8 to obtain a diluted coupling agent solution. Then, 0.3% of the diluted coupling agent solution by mass was sprayed onto the core particles under stirring, and then heated to 45°C and kept at that temperature for 10 minutes. After completion, pretreated particles were obtained.
[0068] (3) Add silane coupling agent (KH550) to an ethylene-vinyl acetate copolymer (VAE) emulsion with a solid content of 40 wt.% and stir until homogeneous to obtain a composite liquid with a coupling agent mass fraction of 0.65%. Then, spray 7% of the composite liquid onto the surface of the pretreated particles while stirring. After completion, heat to 45°C and keep at that temperature for 10 min for drying and curing to obtain Grade I core-shell particles for later use.
[0069] (4) Methyl methacrylate (MMA) and a crosslinking agent (ethylene glycol dimethacrylate) were added to a magnesium aluminum hydrotalcite powder dispersion b with a solid content of 25 wt.% and stirred until homogeneous. The mass ratio of MMA to magnesium aluminum hydrotalcite powder was 1:1, and the crosslinking agent was 4.5% of the mass of MMA. Then, under a nitrogen protective atmosphere, 1.5% of the mass of MMA initiator (ammonium persulfate) was added and the mixture was heated to 70°C and stirred for 6 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid b with a water content of 45 wt.%, wherein the mass ratio of the intercalated modified LDH to the dry matter of VAE in the emulsion was 1:3. Then, while stirring, 5% by mass of the coating liquid b is sprayed onto the surface of the Class I core-shell particles. After completion, the mixture is heated to 65°C and held at that temperature for 2.5 hours for drying and curing to obtain steel slag-based expanded aggregate (e.g. Figure 5 (As shown).
[0070] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 157.9 MPa, 72-hour autogenous shrinkage = 532.4 μm / m.
[0071] Example 6 A method for preparing ultra-high performance concrete material is the same as in Example 2 above, except that the steel slag-based expansive aggregate in this example is prepared using the following method: (1) A coating solution a with a water content of 40 wt.% was formed by mixing magnesium aluminum hydrotalcite powder (LDH), ethylene-vinyl acetate copolymer (VAE) emulsion, and water, wherein the mass ratio of LDH to VAE dry matter in the emulsion was 1:4. Then, 6% by mass of the coating solution a was sprayed onto the surface of the Grade I core-shell particles of Example 1 above under stirring. After completion, the particles were heated to 50°C and kept at that temperature for 15 min for drying and curing to obtain Grade II core-shell particles.
[0072] (2) A coating solution b with a water content of 40 wt.% is formed by mixing magnesium aluminum hydrotalcite powder (LDH), ethylene-vinyl acetate copolymer (VAE) emulsion, and water, wherein the mass ratio of LDH to VAE dry matter in the emulsion is 1:2.5. Then, 4% by mass of the coating solution b is sprayed onto the surface of the Class II core-shell particles of this embodiment under stirring. After completion, the surface is heated to 60°C and kept at that temperature for 3 hours for drying and curing to obtain steel slag-based expanded aggregate (e.g., Figure 6 (As shown).
[0073] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 153.4 MPa, 72-hour autogenous shrinkage = 601.8 μm / m.
[0074] Example 7 A method for preparing ultra-high performance concrete material is the same as in Example 3 above, except that the steel slag-based expansive aggregate in this example is prepared by the following method: (1) A silane coupling agent (KH792), anhydrous ethanol, and water were mixed evenly at a volume ratio of 1:1:8.5 to obtain a diluted coupling agent solution. Then, 0.5% of the diluted coupling agent solution was sprayed onto converter steel slag particles with a particle size distribution between 0.45 and 2 mm under stirring. The mixture was then heated to 55°C and held for 5 minutes to obtain pretreated particles.
[0075] (2) Add silane coupling agent (KH792) to an ethylene-vinyl acetate copolymer (VAE) emulsion with a solid content of 42 wt.% and stir until homogeneous to obtain a composite liquid with a coupling agent mass fraction of 1%. Then, spray 5% of the composite liquid onto the surface of the pretreated particles while stirring. After completion, heat to 55°C and keep at that temperature for 5 min for drying and curing to obtain Grade I core-shell particles for later use.
[0076] (3) Methyl methacrylate (MMA) was added to a magnesium aluminum hydrotalcite powder dispersion a with a solid content of 30 wt.%, and the mass ratio of MMA to magnesium aluminum hydrotalcite powder was 1.5:1. Then, under a nitrogen protective atmosphere, 1.0% of the mass of the MMA initiator (azobisisobutyronitrile) was added, and the mixture was heated to 60°C and stirred for 8 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 200-mesh sieve to obtain PMMA hybrid exfoliated LDH (ExLDH). Then, the exfoliated LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid a with a water content of 60 wt.%, wherein the mass ratio of the exfoliated LDH to the dry matter of VAE in the emulsion was 1:6. Then, 7.5% of the mass of the coating liquid a was sprayed onto the surface of the Class I core-shell particles under stirring. After completion, the mixture was heated to 60°C and kept at that temperature for 10 min for drying and curing to obtain Class II core-shell particles.
[0077] (4) Hydroxyethyl acrylate (HEA) and a crosslinking agent (triethylene glycol diacrylate) were added to a magnesium aluminum hydrotalcite powder dispersion b with a solid content of 20 wt.% and stirred until homogeneous. The mass ratio of HEA to magnesium aluminum hydrotalcite powder was 1.5:1, and the crosslinking agent was 8% of the mass of HEA. Then, under a nitrogen protective atmosphere, 1.0% of the mass of HEA initiator (azobisisobutyronitrile) was added and the mixture was heated to 60°C and stirred for 8 hours. After completion, the solid product was filtered out, washed with anhydrous ethanol, dried, ground, and passed through a 300-mesh sieve to obtain crosslinked polymer intercalated modified LDH (PLDH). The crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer (VAE) emulsion, and water were mixed to form a coating liquid b with a water content of 60 wt.%, wherein the mass ratio of the intercalated modified LDH to the dry matter of VAE in the emulsion was 1:2. Then, while stirring, 7% by mass of the coating liquid b is sprayed onto the surface of the Class II core-shell particles. After completion, the mixture is heated to 70°C and held for 2 hours for drying and curing to obtain steel slag-based expanded aggregate (e.g. Figure 7 (As shown).
[0078] Performance testing: The 28-day compressive strength and 72-hour autogenous shrinkage of the ultra-high performance concrete material prepared in this embodiment were tested using the same method as in Example 1 above. The results were: 28-day compressive strength = 154.7 MPa, 72-hour autogenous shrinkage = 514.2 μm / m.
[0079] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., should be included within the protection scope of the present invention.
Claims
1. A method for preparing a gradient core-shell structured steel slag-based expansive aggregate, characterized in that, Includes the following steps: (1) Provide a core particle with a particle size of 0.45-2mm, which is composed of steel slag powder, calcium-based activator and sulfate in a ratio of 70-80 parts by weight: 5-10 parts by weight: 2-4 parts by weight, for later use; the specific surface area of the steel slag powder is 400-500m² / kg; the calcium-based activator is an active powder with a specific surface area of 450-550m² / kg obtained by calcining limestone at 1200-1400℃ for 5-15min. (2) Apply a coupling agent dilution to the surface of the core particles and heat and keep warm. After completion, apply a composite liquid formed by ethylene-vinyl acetate copolymer emulsion and coupling agent to the surface of the pretreated particles. After drying and curing, obtain Grade I core-shell particles for later use. (3) Methyl methacrylate was added to the magnesium aluminum hydrotalcite powder dispersion a, and then an initiator was added under a protective atmosphere and the mixture was heated and stirred to react. After the reaction was completed, the solid product was separated, washed, dried and ground to obtain PMMA hybrid exfoliated LDH. Then, the exfoliated LDH, ethylene-vinyl acetate copolymer emulsion and water were mixed to form coating liquid a, and the coating liquid a was applied to the surface of the first-level core-shell particles. After drying and curing, the second-level core-shell particles were obtained. (4) Methyl methacrylate and / or hydroxyethyl acrylate and crosslinking agent are added to magnesium aluminum hydrotalcite powder dispersion b and mixed well; then an initiator is added under a protective atmosphere and heated and stirred to react; after completion, the solid product is separated, washed, dried and ground to obtain crosslinked polymer intercalated modified LDH; the crosslinked polymer intercalated modified LDH, ethylene-vinyl acetate copolymer emulsion and water form coating liquid b, and the coating liquid b is applied to the surface of the second-level core-shell particles, dried and cured to obtain the steel slag-based expanded aggregate.
2. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the coupling agent diluent is 0.2-0.5% of the mass of the core particles.
3. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the coupling agent dilution solution is made by mixing coupling agent, anhydrous ethanol and water in a volume ratio of 1:1:7~8.
5.
4. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the heating and heat preservation temperature is 45~55℃ and the time is 5~10min.
5. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the mass fraction of the coupling agent in the composite liquid is 0.5~1%.
6. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the composite liquid is 5-8% of the mass of the pretreated particles.
7. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the solid content of the ethylene-vinyl acetate copolymer emulsion in the composite liquid is 35~42 wt.%.
8. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (2), the drying and curing temperature is 45~55℃ and the time is 5~10min.
9. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the mass ratio of methyl methacrylate to magnesium aluminum hydrotalcite powder in dispersion a is 0.5~1.5:
1.
10. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the solid content of the magnesium aluminum hydrotalcite powder dispersion a is 20~30 wt.%.
11. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the initiator is 0.5 to 1.5% of the mass of methyl methacrylate.
12. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the temperature of the heating and stirring reaction is 60~80℃ and the time is 4~8 hours.
13. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the mass ratio of VAE dry matter in the stripped LDH and ethylene-vinyl acetate copolymer emulsion is 1:4~6.
14. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the water content of the coating liquid a is 40~60 wt.%.
15. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the initiator includes at least one of ammonium persulfate and azobisisobutyronitrile.
16. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the coating liquid a is 6 to 10% of the mass of the Class I core-shell particles.
17. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (3), the drying and curing temperature is 50~60℃ and the time is 10~15min.
18. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the crosslinking agent includes at least one of ethylene glycol dimethacrylate, N,N'-methylenebisacrylamide, triethylene glycol diacrylate, and 1,6-hexanediol diacrylate.
19. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the initiator includes at least one of ammonium persulfate and azobisisobutyronitrile.
20. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the temperature of the heating and stirring reaction is 60~80℃ and the time is 4~8 hours.
21. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the mass ratio of methyl methacrylate and / or hydroxyethyl acrylate to magnesium aluminum hydrotalcite powder in dispersion b is 0.5~1.5:
1.
22. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the solid content of the magnesium aluminum hydrotalcite powder dispersion b is 20~30 wt.%.
23. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the crosslinking agent is 2 to 8% of the mass of methyl methacrylate and / or hydroxyethyl acrylate.
24. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the initiator is 0.5 to 1.5% of the mass of methyl methacrylate and / or hydroxyethyl acrylate.
25. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to any one of claims 1-8, characterized in that, In step (4), the mass ratio of the cross-linked polymer intercalated modified LDH to the VAE dry matter in the ethylene-vinyl acetate copolymer emulsion is 1:2~3.
26. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the water content of the coating liquid b is 40~60 wt.%.
27. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the coating liquid b is 4-7% of the mass of the Class II core-shell particles.
28. The method for preparing gradient core-shell structured steel slag-based expansive aggregate according to claim 1, characterized in that, In step (4), the drying and curing temperature is 60~70℃ and the time is 2~3 hours.
29. An ultra-high performance concrete material, characterized in that, The composition includes the following components in the following proportions: 90-110 parts by weight of cement, 20-30 parts by weight of silica fume, 50-90 parts by weight of fine aggregate, 15-50 parts by weight of steel slag-based expansive aggregate obtained by the preparation method according to any one of claims 1-28, 1.5-4 parts by weight of water-reducing agent, and 10-30 parts by weight of steel fiber.
Citation Information
Patent Citations
Micro-expansive solid waste-based ultra-high performance concrete
CN120664827A
Anti-cracking concrete and production process thereof
CN122010503A